2017
DOI: 10.5306/wjco.v8.i2.151
|View full text |Cite
|
Sign up to set email alerts
|

Bethesda System for Reporting Thyroid Cytopathology: A three-year study at a tertiary care referral center in Saudi Arabia

Abstract: AIMTo stratify the malignancy risks in thyroid nodules in a tertiary care referral center using the Bethesda system.METHODSFrom January, 2012 to December, 2014, a retrospective analysis was performed among 1188 patients (15-90 years) who had 1433 thyroid nodules and fine-needle aspiration at Prince Sultan Military Medical City, Saudi Arabia. All thyroid cyto-pathological slides and ultra sound reports were reviewed and classified according to the Bethesda System for Reporting Thyroid Cytopathology. Age, gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
3
12
2
Order By: Relevance
“…With regard to the risk of malignancy associated with each Bethesda system category on follow-up, higher risks of malignancy in Category I, II, and III have been noted in studies with low number of follow-up cases including our study. [ 2 5 16 17 ] Surprisingly, our study shows the highest risk of malignancy in the benign category compared to the other studies. Some of these studies show even a higher risk of malignancy in Category III compared to Category IV, which is not consistent with TBSRTC proposal of a sequentially increasing implied risk of malignancy.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…With regard to the risk of malignancy associated with each Bethesda system category on follow-up, higher risks of malignancy in Category I, II, and III have been noted in studies with low number of follow-up cases including our study. [ 2 5 16 17 ] Surprisingly, our study shows the highest risk of malignancy in the benign category compared to the other studies. Some of these studies show even a higher risk of malignancy in Category III compared to Category IV, which is not consistent with TBSRTC proposal of a sequentially increasing implied risk of malignancy.…”
Section: Discussioncontrasting
confidence: 86%
“…[ 15 ] Regarding Category III, although the incidence of malignancy is slightly high, it is still within the range reported in the literature which is 6%–50%. [ 12 13 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…We excluded a further 233 studies and finally selected 38 studies, which included 145,066 thyroid nodules, for meta‐analysis (Fig. ) . Among the included studies, 4 were prospective and 34 were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the tools that could prove effective in predicting malignancy in TN assessment include the assessment of the TN size, thyroid-stimulating hormone (TSH) level at the time of diagnosis, Bethesda System for Reporting Thyroid Cytopathology (BSRTC) and Thyroid Imaging Reporting and Data System (TI-RADS). 11 , 12 Consequently, establishing a concordance between the diagnostic procedures (fine-needle aspiration [FNA] and US) might reduce the health care costs as well as numbers of nonessential procedures in the population at risk could be reduced. Findings from various researches also reported that the FNA biopsy must be interpreted precisely to generate a common language among pathologists and surgeons, to enable them to establish a uniform TN management strategy.…”
Section: Introductionmentioning
confidence: 99%